Multimodal exercise program for muscle function improvement in older adults from the Hospital de la Fuerza Aérea del Perú 2018 - falvy bockos, Ian christian (2022)
Objective: To find out the benefits of a multimodal exercise program for muscle function improvement in older adults from the Hospital de la Fuerza Aérea del Perú in 2018. Materials and methods: An interventional, analytical, prospective and longitudinal study. A total of 66 patients were assessed, out of whom only 24 completed the six-month intervention period. Results: The patients’ median age was 75 ± 7.01. The Short Physical Performance Battery (SPPB), which combines the results of the balance, gait speed and chair stand tests, had a positive impact on the intervention group and showed statistically significant results. No statistical significance was found in grip strength in kilograms or calf circumference measurement. Conclusions: The multimodal exercise program for older adults from the Peruvian Air Force has a positive impact on muscle function.